2020
DOI: 10.1097/md.0000000000019626
|View full text |Cite
|
Sign up to set email alerts
|

The role of 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase-3 in esophageal squamous cell carcinoma

Abstract: 6-phosphofructo-kinase-2/fructose diphosphatase-2 isoenzyme 3 (PFKFB3) is closely related to the growth of many types of cancer cells. Glycolysis not only provides Adenosine triphosphate for the growth of tumor cells, but also protects them from acid products, which is beneficial to the invasion and metastasis of tumors. However, PFKFB3 expression in esophageal squamous cell carcinoma (ESCC) has been scarcely reported. In this study, the role of PFKFB3 was studied in 120 ESCC samples using immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Understanding its mechanism of occurrence and development may provide new methods and ideas for the treatment of LUAD; therefore, seeking new molecular prognostic markers is essential. There is growing evidence demonstrating that PFKFB3 plays an important role in promoting tumor progression in different kinds of human cancers, 21 such as ESCC, 22 LUAD. In addition, in our previous study, we have found that PFKFB3 is an oncogene in LUAD tumor progression and concluded that targeting PFKFB3 may become a promising therapy, 23 however, fewer samples were collected, and the clinical value was not analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding its mechanism of occurrence and development may provide new methods and ideas for the treatment of LUAD; therefore, seeking new molecular prognostic markers is essential. There is growing evidence demonstrating that PFKFB3 plays an important role in promoting tumor progression in different kinds of human cancers, 21 such as ESCC, 22 LUAD. In addition, in our previous study, we have found that PFKFB3 is an oncogene in LUAD tumor progression and concluded that targeting PFKFB3 may become a promising therapy, 23 however, fewer samples were collected, and the clinical value was not analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple genes have been implicated in the regulation of cell energy metabolism process in ESC [5,6,12,25,26]. In particular, several EMRGs, such as RAC1 [5], TKTL1 [27], and PFKFB3 [28] were shown to be associated with prognosis in patients with ESC. However, previous studies were limited by just single gene detected, small sample sizes, and lack of independent validation.…”
Section: Discussionmentioning
confidence: 99%